AnimoDrop: Terminal year end report - Dailo, Alyssa Nicole (Animo Repository, 2021)
AnimoDrop is a modified dropshipping service for Lasallian MSMEs that sells Lasallian supplier items on a consignment and wholesale basis. This year-end report shares the experience of the authors as student entrepreneurs.